PEMBERIAN Trichoderma spp. PADA MEDIUM GAMBUT UNTUK MEMACU PERTUMBUHAN SEMAI MERANTI TEMBAGA (Shorea leprosula Miq.) - Mardhiansyah, M.; Arlita, Tuti (PEST Tropical Journal, 2013)
This research aimed to determine the effect of Trichoderma spp. application inpeat medium of Shorea leprosula seedling quality and knowing the bestapplication doses of Trichoderma spp. to increase the growth of Shorea leprosulaseedling. The research used method completely randomized design (CRD) with of5 treatments and 10 replications. The treatment consisted of; T0 = Withoutapplication of Trichoderma spp. 0 gr/polybag; T1 = application of Trichodermaspp. 10 gr/polybag; T2 = application of Trichoderma spp. 20 gr/polybag; T3 =application of Trichoderma spp. 30 gr/polybag; T4 = application of Trichodermaspp. 40 gr/polybag. The research proved that the application of Trichoderma spp.in peat medium can increase the quality of Shorea leprosula seedling. Theapplication of Trichoderma spp. with a doses of 40 gr/polybag in peat medium isthe best treatment to the high growth (2.98 cm), diameter growth (1.56 mm), plantdry weight (3.09 gr) and top root ratio (2.65 gr).Keywords: Shorea leprosula, Trichoderma, peat medium